General Themes and their Effect on Movashehat Prosody - Isa Ibrahim Fares (دراسات في اللغة العربيّة وآدابها)
Many studies have been conducted on the relation between Movashehat (light-hearted poetry) and the mainstream of Arabic poetry. They have expressed different attitudes toward this type of Andalusian poetry. Some studies do not exclude Mvashahat from Arabic poetry; while others regard this poetic type as breaking with mainstream poetry in meter, rhyme, and language. Movashahat, whether according to standard metrical patterns or general themes, is associated with Arabic language in two ways: 1) being related to the language of poetry and fluent Arabic, a point which all agree on, and 2) expressing the popular culture and local motifs in light-hearted manners, which seems against the standards and norms of Arabic poetry. But, this does not mean its complete break with poetry and Movashahat establish an independent tradition in poetry. It is only an experiment in poetic tradition, which wants to defamiliarize against the conventional metrical practices. It is a critical experiment to help development, not a subversive attempt. This research emphasizes the metrical aspects of Movashahat, which is effected through bringing about correspondence between the prosodic patterns of poems and the subject matter.  The study also considers the effect of general and romantic themes and motifs upon which the light-hearted poem (Movashah) is based.